Becoming evil : how ordinary people commit genocide and mass killing - Waller, James (Oxford ; New York : Oxford University Press, 2007)
"With this second edition, James Waller brings us up to date on some of the horrific events he used in the first edition to illustrate his theory of extraordinary human evil, pointing out steps taken both forward and back. Nearly a third of the references are new, reflecting the rapid pace of scholarship in Holocaust and genocide studies, and the issue of gender now occupies a prominent place in the discussion of the social construction of cruelty. Waller also offers a reconfigured explanatory model of evil to acknowledge that human behavior is multiply influenced and that any answer to the question "Why did that person act as he or she did?" can be examined at two levels of analysis - the proximate and the ultimate."--BOOK JACKET
Keywords: Genocide; Social psychology